Appropriation of Images of Antiquity in the Work of Jeff Koons - Shchetinina, Nataliya V. (Actual Problems of Theory and History of Art, 2015)
Using the example of Gazing Ball series this study examines the problem of appropriation in the art of Jeff Koons. The changes of images of antiquity (which have taken place with the appropriation) are analyzed in this article as well as the problems that emerged after the connection of such images with kitsch. In the article attention is drawn not only to the fact of using the appropriation, but the variety of conceptual lines introduced by means of appropriation in the artist’s works. The analysis of these works shows a fundamental strategy that J. Koons follows — the strategy of eliminating elitism of so called “high art” and bringing its legacy to mass-culture. The artist creates intelligible language that any audience can comprehend. This is a lexicon developed from the modes of advertising, kitsch and pop-culture. Combining kitsch and European tradition of art, Koons points out the problem of perception encountering knowledge. The elements of kitsch help the audience to recognize images immediately. Images of familiar and comprehendible things (like those from the supermarket) do not disturb the spectator. The artist refers to the tradition of art considering the level of audience’s sophistication and its ability to understand the specific group of signs that circulate in the media and advertising. J. Koons neutralizes classical images charged with information and puts it in the context of mass culture. The artist creates a steady set of new images and represents the tradition of art in terms of advertising, kitsch and pop-culture, available to the wide audience. Such tactics evoke wide range of issues linked with the coexistence of traditional and contemporary art.
Keywords: appropriation; Jeff Koons; contemporary art; mass culture; advertising